Arthrobacter sp lipase immobilization for preparation of enantiopure masked beta-amino alcohols - Chaubey, Asha; Parshad, Rajinder; Gupta, Pankaj; Taneja, Subhash C.; Qazi, Ghulam N.; Rajan, C. R.; Ponrathnam, S. (Bioorganic & Medicinal Chemistry, 2009)
Recent reports on immobilization of lipase from Arthrobacter sp. (ABL, MTCC 5125; IIIM isolate) on insoluble polymers have shown altered properties including stability and enantioselectivity. Present work demonstrates a facile method for the preparation of enantiopure beta-amino alcohols by modulation of ABL enzyme properties via immobilization on insoluble as well as soluble supports using entrapment/covalent binding techniques. Efficacies of immobilized ABL on insoluble supports prepared from tetraethylorthosilicate/aminopropyltriethoxy silane and soluble supports derived from copolymerization of N-vinyl pyrrolidone-allylglycidyl ether (ANP type)/N-vinyl pyrrolidone-glycidyl methacrylate ( GNP type) for kinetic resolution of masked beta-amino alcohols have been studied vis-a-vis free ABL enzyme/wet cell biomass. The immobilized lipase on different insoluble/soluble supports has shown 21 - 110 mg/g protein binding and 30 - 700 U/g activity for hydrolyzing tributyrin substrate. The findings have shown a significant enhancement in enantioselectivity (ee 99%) vis-a-vis wet cell biomass providing ee 70-90% for resolution of beta-amino alcohols. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Arthrobacter sp lipase; beta-Aminoalcohol; Enantioselectivity; Immobilization; soluble polymer

Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies

Adsorption of strontium (II) metal ions using phosphonate-functionalized polymer - Bhosle, S. M.; Ponrathnam, S.; Tambe, S. S.; Chavan, N. N. (Bulletin of Materials Science, 2016)
Diethyl[3-(methoxydimethylsilyl)propyl]phosphonate (DMPP) polymer was synthesized for the strontium (II) metal ion recovery using diethylallylphosphonate as staring material. Diethylallylphosphonate was reacted with poly(methylhydro)siloxane (MW 1900-2000 g mol (-1) ) in the presence of Speier's catalyst. The synthesized monomer was characterized by IR, (1) H NMR, (1 3) C NMR and FT-IR spectroscopy techniques, and the synthesized polymers were characterized by IR and NMR spectroscopy, differential scanning calorimetry, thermogravimetric analysis and solubility. The synthesized polymer was used for sequestering strontium metal from the aqueous solution. The metal binding was examined by the energy dispersive spectroscopy and scanning electron microscopy for the adsorbed Sr(II). Batch adsorption studies were performed by varying three parameters, namely initial pH, adsorbent dose and the contact time. The reaction kinetics was determined by the Langmuir, Freundlich, and pseudo-first- and second-order models. Results of this study indicate that the synthesized polymer DMPP has been effective in removing Sr(II) from the aqueous solution.